Dampak Proses Liminalitas pada Aktivitas Sosial Ekonomi Pedagang Pasar Jongke Surakarta - Whiemhazathissy, Uchffinauzhien Rienafrighni; Nurhadi, Nurhadi (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2024)
Market revitalization is one of the flagship programs of the Surakarta government in eliminating the negative stigma of traditional markets. Jongke Market is one of the traditional markets that is carried out by the revitalization process so that it requires the traders to be relocated in order to facilitate the development process. This research will examine the social and economic impacts that arise due to the liminality process in the revitalization of Jongke Market. Qualitative method with descriptive approach is used in this research. The informants of this research are traders and buyers in Jongke Market. Data were obtained through an interview process and then analyzed through the Miles and Huberman interactive model. The results showed that the liminality process in Jongke market revitalization had a social impact in the form of fading social relationships of traders which resulted in social change, norm change, the emergence of ambiguity due to the repeated adaptation process, to the emergence of conflict. This impact affects the economic activities of traders because the small size of stalls results in reduced bargaining power of traders, the unstrategic location of stalls reduces customers, increases production capital, and reduces income. The destructive liminality process results in an economic crisis for traders.